Linking Green HRM to Green Competitive Advantage: The roles of Green Leadership and Green Organizational Identity in Batam Hotels - Evi Silvana Muchsinati; Icha Heriaty Togatorop; Muhammad Donal Mon; Noor Fareen Abdul Rahim (Business Management Analysis Journal (BMAJ), 2026)
This study aims to evaluate the mediating roles of green leadership and green organizational identity in enhancing the effectiveness of green human resource management toward green competitive advantage in the hospitality sector. Hypothesis testing was conducted using Smart PLS 4.0 involving 273 employees from four-star hotels in Batam City. The findings reveal that green leadership and green organizational identity play significant mediating roles in strengthening the relationship between green human resource management and green competitive advantage. However, this study is limited to four-star hotels in Batam City, which restricts the generalizability of the results to other regions or hotel categories. Future research is recommended to expand the geographical scope and employ a longitudinal approach to provide a more comprehensive understanding of the dynamic relationships among the studied variables over time.